Serial reproduction of narratives preserves emotional appraisals. Issue 4 (19th May 2022) - Breithaupt, Fritz; Li, Binyan; Kruschke, John K.
ABSTRACT: We conducted the largest multiple-iteration retelling study to date (12, 840 participants and 19, 086 retellings) with two different studies that test how emotional appraisals are transmitted across retellings. We use a novel Bayesian model that tracks changes across retellings. Study 1 examines the preservation of appraisals of happy and sad stories and finds that retellings preserve the story's degree of happiness and sadness even when length shrinks and aspects of story coherence and rationalisation deteriorate. Study 2 compared the transmission of appraisals of happiness and sadness with embarrassment, disgust, and risk. Appraisals of happiness, sadness, and also embarrassment showed high appraisal preservation, while disgust and risk were not well preserved. We conclude that participants in our studies encoded happy and sad stories by encapsulating the events and details into an overall emotional appraisal of the story and that this processing strategy might also apply to stories involving other emotions like embarrassment. The emotional appraisal played a key role in retelling by helping to guide the selection, invention, and ordering of the story elements. Hence, we posit that emotion appraisals can operate as anchors for remembering and retelling stories, thus playing an important role in narrative communication.